TEMPORO-SPECTRAL COHERENT STRUCTURE OF TURBULENCE AND PRESSURE USING FOURIER AND WAVELET TRANSFORMS - Thai-Hoa Le; Dong-Anh Nguyen (Universitas Gadjah Mada, 2008)
Studying the spatial distribution in coherent fields such as turbulent and turbulent-induced force ones is important to model and evaluate turbulent-induced forces and response of structures on the turbulent flows. Turbulent field-based coherent function is commonly used for the spatial distribution characteristic of induced forces in the frequency domain. This paper will focus to study spectral coherent structure of turbulence and forces in not only the frequency domain using conventional Fourier transform-based coherence, but also temporo-spectral coherent one in the time-frequency plane thanks to wavelet transform-based coherence for more understanding of the turbulence and force coherences and their spatial distributions. Effects of spanwise separations, bluff body flow and flow conditions on coherent structures of turbulence and induced pressure, comparison between turbulence and pressure coherences as well as intermittency of coherent structure in the time-frequency plane will be investigated here.